THE INFLUENCE OF THE PHYSICAL WORK ENVIRONMENT ON WORK SPIRIT AT THE REGIONAL WATER DRINKING COMPANY (PDAM) TABALONG - Wahyuni; Indriati Sumarni (JAPB, 2023)
The purpose of this study was to determine: 1) the effect of the physical work environment on employee morale at PDAM Tabalong; and 2) how much influence the physical work environment has on morale at PDAM Tabalong. The sample technique uses saturated sampling. The population is 65 employees and 65 respondents at PDAM Tabalong. Data collection techniques include a questionnaire using a modified Likert scale. The research approach uses quantitative methods with an associative approach. The test tool used is SPSS version 26. Test the hypothesis by t-testing the hypothesis. The results of the Simple Linear Regression Analysis Test on the effect of the physical work environment (X) on employee morale at PDAM Tabalong concluded that the physical work environment has no effect on employee morale. As well as the results of the t-test, it is known that the Tcount value is 1.634, which is smaller than the ttable value of 1.669 (1.634 1.669), with a significance of 0.071 greater than 0.05 (0.071 > 0.05). It can be concluded that the physical work environment has no effect on employee morale at PDAM Tabalong because the tcount is smaller than the ttable and the significant value is greater than 0.05, so Ho is accepted and Ha is rejected. The magnitude of the relationship value (R) is equal to 0.0225. From this output, the coefficient of determination (R square) is 0.051, or 5.1%, and the adjusted R square value is 0.036, which means that the influence of the physical work environment on employee morale at PDAM Tabalong is 3.6%, the remaining 96%. 4% is influenced by other variables outside of the variables tested. The value is taken from the adjusted R square because the sample is less than 100 (Pallan, 2011). Keywords: Physical Work Environment and Employee Morale